1994
DOI: 10.1128/aac.38.3.415
|View full text |Cite
|
Sign up to set email alerts
|

Cefepime compared with ceftazidime as initial therapy for serious bacterial infections and sepsis syndrome

Abstract: In an open randomized multicenter comparative study, we evaluated the safety and efficacy of cefepime (CP; 2.0 g given intravenously every 12 h) and ceftazidime (CZ; 2.0 g given intravenously every 8 h) as initial treatment for adult patients with suspected serious bacterial infections. A total of 133 patients entered the study, of whom 114 were evaluable for clinical and microbiological response assessment: 56 received CP and 58 received CZ. About 50%o (30 who received CP and 25 who received CZ) fulfilled the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

1998
1998
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(9 citation statements)
references
References 28 publications
0
9
0
Order By: Relevance
“…Cefepime appeared to have clinically equivalent efficacy and safety to comparator antibiotics in a variety of infections such as pneumonia [56], sepsis [57], Gram-negative bacteraemia [58], peritonitis (when combined with metronidazole) [59,60] and lower respiratory tract infections both in adults and children [61,62]. Several randomised trials suggested equivalence between cefepime and comparator antibiotics as monotherapy for neutropenic sepsis, including paediatric patients [63][64][65].…”
Section: Clinical Efficacy Of Cefepimementioning
confidence: 96%
“…Cefepime appeared to have clinically equivalent efficacy and safety to comparator antibiotics in a variety of infections such as pneumonia [56], sepsis [57], Gram-negative bacteraemia [58], peritonitis (when combined with metronidazole) [59,60] and lower respiratory tract infections both in adults and children [61,62]. Several randomised trials suggested equivalence between cefepime and comparator antibiotics as monotherapy for neutropenic sepsis, including paediatric patients [63][64][65].…”
Section: Clinical Efficacy Of Cefepimementioning
confidence: 96%
“…Kieft et al [27] compared cefepime with ceftazidime as initial therapy for patients with sepsis syndrome due to serious bacterial infections in 114 patients. The authors observed a trend towards superior efficacy of cefepime, although this difference did not achieve statistical significance.…”
Section: Gram-negative Activitymentioning
confidence: 99%
“…Colitis (including pseudomembranous colitis), diarrhea, fever, headache, nausea, oral moniliasis, pruritus, urticaria, vaginitis and vomiting were observed in less than 1% of patients. At the higher dose of 2 g every 6-8 h, the incidence of probably related adverse events was higher: rash (4%), diarrhea (3%), nausea (2%), vomiting (1%), pruritus (1%), fever (1%) and headache (1%) [47,60,92,93,113-115]. …”
Section: Safety and Tolerabilitymentioning
confidence: 99%